Understanding the gap between the United Nations world food programme crisis mapping operations and crowdsourcing technology - Richards, S.; Veenendaal, Bert (2014)
There is increasing pressure from the crisis mapping community for United Nations agencies to adopt crowdsourcing technology as part of existing United Nations crisis mapping, emergency response operations. Whilst United Nations agencies such as the World Food Programme are in support of crowdsourcing initiatives, it is imperative that the technology be assessed before it can be adopted as part of the existing crisis mapping operations. It is frequently argued in theoretical scientific papers that during a crisis situation, the limitations associated with crowdsourcing technology are outweighed by the benefits of its use. However, it can also be argued that in crisis mapping operations, crowdsourcing technology is not of sufficient maturity at present to provide adequate benefits. To understand the capability of crowdsourcing technology for crisis mapping, this was tested by evaluating a number of existing crowdsourced applications. Results of this research indicate that crowdsourcing technology is in its infancy and current applications do not meet the expectations required by the World Food Programmes' crisis mapping operations.